(untitled) (Research, Society and Development, 2022)
Introduction: health professionals carry out activities that require physical proximity to the patient, manipulate instruments potentially capable of causing this type of accident, creating opportunities for consequences and directly affecting the physical, psychological and social aspects. General objective: to analyze accidents with biological material among health professionals in the State of Alagoas, in the years 2016 to 2021. Results/discussion: It is noticed that the year 2017 was the one that presented the fewest cases and the year 2019 presented the highest number of cases; Regarding gender, the study showed that females are present in a greater number of cases; The results presented show a predominance of exposure to biological material with health professionals aged between 20 and 29 years; Mid-level health professionals: Nursing technicians 757 (60.1). With regard to higher education health professionals, Nurses 116 (9.3); percutaneous exposure, followed by the circumstance of improper disposal and manipulation of the piercing/cutting box, presented the highest number of cases. nursing professionals are the group related to a greater number of accidents, which is due to the fact that they provide assistance in close physical proximity to the patient, in addition to handling various materials and equipment, with risks to occupational exposure, thus making them, more susceptible to accidents with biological material. Final considerations: Occupational accidents with exposure to biological material are still constant in the state of Alagoas. The need for educational interventions in health is evident, aimed at preventive actions to promote workers’ health and prevent injuries in all categories and activities of health professionals.